2005
DOI: 10.3987/com-05-10484
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for the Synthesis of 1-Substituted β-Carboline Derivatives from Tryptamine and Carboxylic Acids in Polyphosphoric Acid

Abstract: A number of 1-substituted 3,4-dihydro-9H-β-carboline derivatives (4) with high purity and yields have been synthesized by treating of tryptamine (1) with carboxylic acids (2) in polyphosphoric acid. 3,4-Dihydro-9H-β-carbolines (4) were successfully transformed to 1,2,3,4-tetrahydro-9H-β-carbolines (5) and 9H-β-carbolines (6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Racemic screening hit 6 was obtained via alkylation of the readily accessible racemic unsubstituted amine 5a with 2-bromoethanol, and screening hit 7b was similarly obtained by alkylation of 5a with methyl 3-bromopropionate and subsequent hydrolysis of ester 7a (Scheme ). Synthesis of trans- 1 R ,3 R compounds containing a methyl group of defined stereochemistry adjacent to the tetrahydropiperidine nitrogen atom commenced with the appropriate chiral α-methyltryptamine (Schemes –).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Racemic screening hit 6 was obtained via alkylation of the readily accessible racemic unsubstituted amine 5a with 2-bromoethanol, and screening hit 7b was similarly obtained by alkylation of 5a with methyl 3-bromopropionate and subsequent hydrolysis of ester 7a (Scheme ). Synthesis of trans- 1 R ,3 R compounds containing a methyl group of defined stereochemistry adjacent to the tetrahydropiperidine nitrogen atom commenced with the appropriate chiral α-methyltryptamine (Schemes –).…”
Section: Resultssupporting
confidence: 87%
“…A solution of 1-(4-chlorophenyl)-2,3,4,9-tetrahydro-1 H -pyrido­[3,4- b ]­indole ( 5a ) (956 mg, 3.4 mmol), methyl 3-bromopropanoate (1.1 mL, 10.2 mmol), and triethylamine (1.4 mL, 10.2 mmol) in MeCN (1.5 mL) was sealed in a microwave tube. The solution was heated at 140 °C for 3 h in a microwave reactor, then evaporated to dryness and the residue was purified by reverse phase chromatography, with elution gradient 55–100% MeCN in water containing 1% ammonium hydroxide, to give 7a (950 mg, 76%) as a beige solid.…”
Section: Methodsmentioning
confidence: 99%
“…1-Phenyl-9 H -pyrido­[3,4- b ]­indole ( 3aa ): yield 52% (25.4 mg), compound 3aa was reported previously; yellow solid; mp = 240–242 °C; IR (KBr) ν max 2361, 1623, 1559, 1494, 1456, 1416, 1321, 1276, 1233, 736 cm –1 ; 1 H NMR (600 MHz, DMSO- d 6 ) δ 11.54 (s, 1H), 8.46 (d, J = 4.8 Hz, 1H), 8.26 (d, J = 7.8 Hz, 1H), 8.11 (d, J = 4.8 Hz, 1H), 8.08–7.97 (m, 2H), 7.66 (d, J = 8.4 Hz, 1H), 7.61 (t, J = 7.8 Hz, 2H), 7.54 (dt, J = 14.8, 7.8 Hz, 2H), 7.26 (t, J = 7.2 Hz, 1H). 13 C NMR (150 MHz, DMSO- d 6 ) δ 142.2, 141.1, 138.4, 133.0, 129.2, 128.8, 128.6, 128.4, 128.2, 121.6, 120.9, 119.6, 113.9, 112.5.…”
Section: Methodsmentioning
confidence: 64%
“…12 Utilizing this, we have shown that the reaction of 2-(3,4-dimethoxyphenyl)ethylamine with carboxylic acids, their esters or anhydrides in PPA affords the corresponding 3,4-dihydroisoquinolines in very good yields and purity. 14 In this paper we describe acylation of homoveratrylamine (1) with 2-aminobenzoic acid (2) in PPA, leading to a direct formation of 1-(2aminophenyl)-3,4-dihydroisoquinoline, which is known to be a good ligand for cis-platinum(II) antitumor complexes. 14 In this paper we describe acylation of homoveratrylamine (1) with 2-aminobenzoic acid (2) in PPA, leading to a direct formation of 1-(2aminophenyl)-3,4-dihydroisoquinoline, which is known to be a good ligand for cis-platinum(II) antitumor complexes.…”
Section: Resultsmentioning
confidence: 99%